Historical geography I: What remains?. (December 2014) - McGeachan, Cheryl
This report uses the First World War as a way to open up current debates into issues of bodies, selves, battlefields, memory and death in historical geography and beyond. Sweeping through a range of scales, from the global nature of imperialist practices to the intimate spaces of the psyche, this report highlights the contributions that historical geographers are making to these studies and the creative approaches taken. The aim is to expose the need for historical geography to engage with the darkest corners of human experience, in relation to conflict, so as to learn from the past in present insecure times.